PENGARUH STRES KERJA DAN LINGKUNGAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN: (Studi Kasus Pada PT. Bintang Indokarya Gemilang Kabupaten Brebes) - Imam Syafii; Ari Kristiana; Azizah Indriyani (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
This study aims to determine the effect of work stress and work environment on employee turnover intention at PT Bintang Indokarya Gemilang located in Tanjung District, Brebes Regency. This research applies quantitative methods. There are as many as 2.562 employees as the population in this study. A total of 100 respondents were used as a sample which was obtained by calculating using the slovin formula. Data were collected through questionnaires distributed to respondents online using Google Form. Data analysis was carried out with the help of SPSS version 26.0 using several tests including validity, reliability, classical assumptions, multiple linear regression, t test, F test, and coefficient of determination. This study found that work stress partially has a significant influence on turnover intention. Likewise, the work environment partially has a significant influence on turnover intention. In addition, work stress and work environment simultaneously have a significant influence on turnover intention.